The development direction and challenges of STEM integration: a systematic literature review - Zhang Lei; Nur Atiqah Jalaludin; Mohamad Sattar Rasul; Mohamad Hidir Mhd Salim (Journal of Education and Learning (EduLearn), 2026)
The development of society has put forward higher requirements for K-12 talent cultivation. However, some situations are not optimistic, such as students’ low interest in mathematics, science and other disciplines, and the subject setting cannot match the needs of talent cultivation. Numerous studies confirmed that in the context of curriculum integration, further integration of science, technology, engineering, and mathematics (STEM) curriculum, learning methods and other aspects is needed, but there are still few summaries of the development direction and approaches of STEM in the context of STEM integration. This paper focuses on STEM integration, to clarify the development direction and approaches of STEM integration in the context of education reform, and then systematically summarize the development and existing problems of STEM integration education with a systematic literature review (SLR) method, 62 articles from 2013-2023 were finally selected from Web of Science (WoS). This study reveals the development of STEM curriculum, STEM pedagogy and models in STEM integration, attaches importance to the concept of interdisciplinary integration, advocates curriculum integration and improves students’ 21st century skills by integrating. In addition, there needs to be more research focusing on the internal impacts of learning outcomes, STEM literacy, and student STEM identity.